Lanthanides as NMR/MRI temperature sensors and probes of moderately fast molecular dynamics in aqueous medium: A dependence of activation energy of racemization in complexes of diethylenetriaminepentaacetat on lanthanide ion; Sensors and Actuators B: Chemical; Vol. 251 - Babailov S. P. Sergey Pavlovich (2017, 2017)
Title screen